THE EFFECT OF DIVIDEND POLICY AND DEBT ON COMPANY VALUE: (Empirical Study on Manufacturing Companies on the Indonesia Stock Exchange 2003 - 2016) - S. Syahyono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
In a business, a lack of capital is not impossible. To overcome this, the company will usually borrow capital from the bank. This is done to get additional capital. In addition, companies can also get additional capital from individual investors. This study uses a quantitative approach. The results of this study dividend policy influence on firm value Dividend policy and debt policy affect firm value in manufacturing companies on the Indonesia Stock Exchange in 2003-2016.